Effect of hydroalcoholic extract of flaxseed on bone mineral density in Wistar rats using digital radiography - Nozari Moshtaghin, Farideh (Caspian J Intern Med, 2020)
BACKGROUND: Given that the world's population is aging, the problems associated with osteoporosis and related fractures are increasing. The aim of the study was to evaluate the effect of flaxseed extract on bone mineral density (BMD) in Wistar rats using digital radiography. METHODS: In this experimental study, 25 male and 25 female Wistar rats were randomly divided into 5 groups: 1. Control, 2. Calcium and vitamin D (Ca/VitD), 3. 100 mg/kg flaxseed, 4. 200 mg/kg flaxseed, and 5. 400 mg/kg flaxseed. Then, the animals were kept for thirty days. Maxillary and mandibular BMD as well as serum levels of calcium, vitamin D and phosphorus were measured at baseline and after 30 days of keeping the rats. RESULTS: The results showed that serum levels of calcium and phosphorus were not significantly different in all five groups before and after 30 days. Serum levels of vitamin D were significantly higher in the group receiving Ca/vit D (with a mean of 61.6±15.8 in the male group and 85±12.9 in the female group) as compared with other groups (P<0.001). The highest level of change in maxillary and mandibular bone density was in 200 mg/kg flaxseed group with a mean difference of 24.5±6.1 and 26.5±3.1, respectively, which was significant in comparison with the control and Ca/vit D groups (p<0.001) . CONCLUSION: Flaxseed extract is more effective in increasing bone density than the group receiving Ca/vit D. The mandibular and maxillary BMD was higher in the group receiving 200 mg/kg flaxseed compared to the group receiving Ca/vit D (p<0.001).